Spatiotemporal patterns of gene expression during development of a complex colony morphology. - Gareth A Cromie; Zhihao Tan; Michelle Hays; Amy Sirr; Aimée M Dudley (PLoS ONE)
Clonal communities of single celled organisms, such as bacterial or fungal colonies and biofilms, are spatially structured, with subdomains of cells experiencing differing environmental conditions. In the development of such communities, cell specialization is not only important to respond and adapt to the local environment but has the potential to increase the fitness of the clonal community through division of labor. Here, we examine colony development in a yeast strain (F13) that produces colonies with a highly structured "ruffled" phenotype in the colony periphery and an unstructured "smooth" phenotype in the colony center. We demonstrate that in the F13 genetic background deletions of transcription factors can either increase (dig1D, sfl1D) or decrease (tec1D) the degree of colony structure. To investigate the development of colony structure, we carried out gene expression analysis on F13 and the three deletion strains using RNA-seq. Samples were taken early in colony growth (day2), which precedes ruffled phenotype development in F13, and from the peripheral and central regions of colonies later in development (day5), at which time these regions are structured and unstructured (respectively) in F13. We identify genes responding additively and non-additively to the genotype and spatiotemporal factors and cluster these genes into a number of different expression patterns. We identify clusters whose expression correlates closely with the degree of colony structure in each sample and include genes with known roles in the development of colony structure. Individual deletion of 26 genes sampled from different clusters identified 5 with strong effects on colony morphology (BUD8, CIS3, FLO11, MSB2 and SFG1), all of which eliminated or greatly reduced the structure of the F13 outer region.